2019
DOI: 10.1186/s12894-019-0553-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparative effectiveness analysis of the PBCG vs. PCPT risks calculators in a multi-ethnic cohort

Abstract: BackgroundPredictive models that take race into account like the Prostate Cancer Prevention Trial Risk Calculator 2.0 (PCPT RC) and the new Prostate Biopsy Collaborative Group (PBCG) RC have been developed to equitably mitigate the overdiagnosis of prostate specific antigen (PSA) screening. Few studies have compared the performance of both calculators across racial groups.MethodsFrom 1485 prospectively recruited participants, 954 men were identified undergoing initial prostate biopsy for abnormal PSA or digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…In either case, the most pressing need with respect to disparities research is validation of predictive models in non-White populations. Most existing PCa prognostic tools were developed using data for men of European ancestry; these may be acceptably accurate across diverse populations, but without sufficient data capture to permit validation efforts, we cannot be sure that use of such models in non-White populations is not exacerbating disparities [62]. For future studies, biomarker discovery and model training that focuses on or explicitly oversamples from Black and other non-White populations will lead to more equitable and reliable prognostic models across heterogeneous populations.…”
Section: 4mentioning
confidence: 99%
“…In either case, the most pressing need with respect to disparities research is validation of predictive models in non-White populations. Most existing PCa prognostic tools were developed using data for men of European ancestry; these may be acceptably accurate across diverse populations, but without sufficient data capture to permit validation efforts, we cannot be sure that use of such models in non-White populations is not exacerbating disparities [62]. For future studies, biomarker discovery and model training that focuses on or explicitly oversamples from Black and other non-White populations will lead to more equitable and reliable prognostic models across heterogeneous populations.…”
Section: 4mentioning
confidence: 99%
“…Carbunaru et al explored the effectiveness of these calculators in a multi-ethnic cohort and found the AUC for clinically significant Prostate Cancer was lower than the originally published articles at 64% (95% CI 0.61–0.68) for PCPT and 65% (95% CI 0.62–0.68) for PBCG [ 14 ]. A limiting factor of using these more established scoring systems, is that they may not reflect the Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the ERSPC‐RC was found to be poorer than the MRI‐ERSPC‐RC with Radtke et al, Mortezavi et al, Poyet et al, and Lundon et al describing an AUC of 0.77, 0.8, 0.73, and 0.69, respectively, for estimating the risk of significant PCa 22,25‐27 . The performance of the PBCG‐RC has previously been evaluated with Saba et al identifying an AUC of 0.69, Mortezavi et al finding an AUC of 0.76, and Carbunaru et al identifying an AUC of 0.65 for the detection of clinically significant PCa 24,25,28 . These studies were all performed in European or American populations, whereas our study was the first validation study performed in an Australian population.…”
Section: Discussionmentioning
confidence: 99%
“…7 Our results are comparable to other validation studies of the MRI- 22,[25][26][27] The performance of the PBCG-RC has previously been evaluated with Saba et al identifying an AUC of 0.69, Mortezavi et al finding an AUC of 0.76, and Carbunaru et al identifying an AUC of 0.65 for the detection of clinically significant PCa. 24,25,28 These studies were all performed in European or American populations, whereas our study was the first validation study performed in an Australian population. The consistency demonstrated across these validation studies with the present study suggests that these risk calculators may potentially be utilized in other populations of men for risk stratification of significant PCa.…”
Section: Re Sultsmentioning
confidence: 99%